Bayesian sparsity estimation in compressive sensing with application to MR images. Issue 4 (2nd October 2019) - Wang, Jianfeng; Zhou, Zhiyong; Garpebring, Anders; Yu, Jun
Abstract: The theory of compressive sensing (CS) asserts that an unknown signal x ∈ C N can be accurately recovered from m measurements with m ≪ N provided that x is sparse. Most of the recovery algorithms need the sparsity s = ‖ x ‖ 0 as an input. However, generally s is unknown, and directly estimating the sparsity has been an open problem. In this study, an estimator of sparsity is proposed by using Bayesian hierarchical model. Its statistical properties such as unbiasedness and asymptotic normality are proved. In the simulation study and real data study, magnetic resonance image data is used as input signal, which becomes sparse after sparsified transformation. The results from the simulation study confirm the theoretical properties of the estimator. In practice, the estimate from a real MR image can be used for recovering future MR images under the framework of CS if they are believed to have the same sparsity level after sparsification.